2018
DOI: 10.4038/cjs.v47i4.7555
|View full text |Cite
|
Sign up to set email alerts
|

Population size and movements of the Greater Flamingo (<i>Phoenicopterus</i> <i>roseus</i>) in the Jaffna peninsula, Sri Lanka: Results from a long-term study

Abstract: The Greater Flamingo (Phoenicopterus roseus) is an uncommon migrant bird species found in Sri Lanka, and is a major attraction among avitourists. Jaffna Peninsula, Mannar Island, and the southeastern coastal areas are the known strongholds of this species in Sri Lanka. Previous studies on this species in the Jaffna Peninsula are limited, most probably due to the inaccessibility of the area during the three-decade long civil war. Hence, the objectives of the present study were to determine the population size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The six flamingo species have been frequently, but not unanimously (see below), considered migratory (Espino- Barros & Baldassarre 1989, McCulloch et al 2003, Johnson & Cézilly 2007, Sanz-Aguilar et al 2012, Béchet 2016, Wijesundara et al 2018. Indeed, these birds appear to possess variable types of movements that do not match the abovementioned attributes required to be considered strictly migratory (cf.…”
Section: Flamingo Movementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The six flamingo species have been frequently, but not unanimously (see below), considered migratory (Espino- Barros & Baldassarre 1989, McCulloch et al 2003, Johnson & Cézilly 2007, Sanz-Aguilar et al 2012, Béchet 2016, Wijesundara et al 2018. Indeed, these birds appear to possess variable types of movements that do not match the abovementioned attributes required to be considered strictly migratory (cf.…”
Section: Flamingo Movementsmentioning
confidence: 99%
“…Another order frequently considered migratory is the Phoenicopteriformes (e.g. McCulloch et al 2003, IUCN 2018, Somenzari et al 2018, Wijesundara et al 2018, which comprises six extant species of flamingos in three genera: Phoenicopterus, Phoeniconaias and Phoenicoparrus (Winkler et al 2020, Gill et al 2021. Four species occur in the Americas: Caribbean (American) Flamingo Phoenicopterus ruber, Chilean Flamingo P. chilensis, Andean Flamingo Phoenicoparrus andinus and Puna (James's) Flamingo P. jamesi, whereas Greater Flamingo Phoenicopterus roseus and Lesser Flamingo Phoeniconaias minor occur in Eurasia and Africa (Winkler et al 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times most of the published researches focused on diversity and abundance of waterbirds in the northern region, Sri Lanka. Studies have identified considerable number of birding areas with a high avitourism potential in the northern region of Sri Lanka (Kandasamy et al, 2016;Kandasamy et al, 2017a;Kandasamy et al, 2017b;Kandasamy et al, 2017c;Kandasamy et al, 2017d;Kandasamy et al, 2018;Rajkumar and Wijesundara, 2014;Rajkumar and Wijesundara, 2015a;Rajkumar and Wijesundara, 2015b;Rajkumar and Wijesundara, 2017;Wijesundara and Rajkumar, 2016;Wijesundara et al, 2018).…”
Section: Future Directions and Research Prioritiesmentioning
confidence: 99%
“…Although bird-related studies have been undertaken in the northern region of Sri Lanka (Kandasamy et al, 2016;Kandasamy et al, 2017a;Kandasamy et al, 2017b;Kandasamy et al, 2017c;Kandasamy et al, 2017d;Kandasamy et al, 2018;Rajkumar and Wijesundara, 2014;Rajkumar and Wijesundara, 2015a;Rajkumar and Wijesundara, 2015b;Rajkumar and Wijesundara, 2017;Wijesundara and Rajkumar, 2016;Wijesundara et al, 2018) waterbird communities have not been studied in many areas in the northern region of Sri Lanka as the area was inaccessible for three decades due to the armed conflict. Hence the present study was conducted to document the diversity and abundance of waterbirds in these districts and to find out the possibilities of ecotourism in selected areas in this region.…”
Section: Introductionmentioning
confidence: 99%